1984
DOI: 10.1111/j.1751-1097.1984.tb03899.x
|View full text |Cite
|
Sign up to set email alerts
|

MODIFYING FACTORS OF THE CELLULAR CONCENTRATION OF PHOTOLYASE MOLECULES IN Saccharomyces cerevisiae CELLS–I. EFFECTS OF TEMPERATURE AND LIGHT

Abstract: Abstract— The effects of temperature and light on the cellular concentration of photoreactivating enzyme (PRE) molecules in haploid Saccharomyces cerevisiae cells were investigated. (1) Temperature effect: The number of active PRE molecules per cell (NPRE) in cells grown at 37°C was about 13% of that grown at 23°C, although the amount of proteins per cell remained the same. (2) Light effect: NPRE in cells grown in light was about 2.8 times larger than that grown in the dark. The value of NPRE in cells grown in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In the previous paper (Fukui and Laskowski, 1984) it has also been shown that &REact in stat-cells grown in the dark at 23, 30 or 37°C is 229, 92 and 31, respectively. This difference of NpREact in stat-cells grown a t various temperatures can hardly be explained solely by thermodynamic inactivation of active P R E molecules.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In the previous paper (Fukui and Laskowski, 1984) it has also been shown that &REact in stat-cells grown in the dark at 23, 30 or 37°C is 229, 92 and 31, respectively. This difference of NpREact in stat-cells grown a t various temperatures can hardly be explained solely by thermodynamic inactivation of active P R E molecules.…”
Section: Discussionmentioning
confidence: 79%
“…This preillumination effect agrees with the thermal stability-effect of preillumination on PR activity of active PRE molecules reported by Harm and Rupert (1976). In the previous paper the effect of continuous light-illumination on N p~E was investigated (Fukui, Laskowski, 1984). The N~R E~~~ of stat-cells grown in the dark at 30°C was about 90.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physiological changes are brought about by factors that are assumed not to damage DNA directly but to induce DNA repair ability, such as growth inhibition, temperature shift and depletion of nutrition (4,5). Regarding the SOS response and the adaptive responses in bacteria, there are many detailed reports on the molecular mechanisms for the induction of DNA repair ability (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%